SISTEM INFORMASI GEOGRAFIS POTENSI EKONOMI DAERAH PROVINSI SULAWESI TENGGARA MENGGUNAKAN FUZZY C-MEANS CLUSTERING - Wa ode Sri Wulan; Sutardi Sutardi; LM Tajidun (Informatics Engineering Department of Halu Oleo University, 2018)
Southeast Sulawesi Province consists of 15 districts and 2 cities. The economy of a region can be seen from the potentials that exist in the area. To obtain information on Regional Economic Potentials of Southeast Sulawesi Province can visit the Central Bureau of Statistics (BPS) of Southeast Sulawesi Province. Problems that occur usually people only get data numbers in the form of tables that are less informative so that less information can be caught.Therefore, to implement this application used Fuzzy C-Means Clustering method in grouping regional economic potential by utilizing Geographic Information System into a software.By using Fuzzy C-Means clustering to facilitate the clustering of an area with the largest, medium and low economic result and measure the accuracy level. The result is a visualization overview which shows the grouping of regions based on the economic results of Southeast Sulawesi.Keywords— Fuzzy C-means Clustering, GIS, Economic Potential.DOI : 10.5281/zenodo.1402840